Stakeholder Partnership in the Management of Marine Tourism in South Lampung Regency, Lampung - Rahayu Sulistiowati; Meiliyana Meiliyana; Syamsul Ma’arif; Selvi Diana Meilinda (Lasigo Akademia Indonesia, 2020)
Tourism management must involve stakeholders who each play a role in increasing tourist visits. Although several research have been pointed out the stakeholder’s role in tourism management, the research on the context of marine tourism is still a few. This research aims to analyze stakeholder partnerships in the management of marine tourism in Lampung Selatan Regency. It is important to map engaged actors in the tourism management. The results show that there are 12 stakeholders who partnered and had their respective roles. Stakeholders involved in the management of nature tourism based on interests and influences in South Lampung consist of: a) Key Player, namely Tourism Agency; b) Subject, namely PT Kahaii (Private company) and the community who own beach tourism objects, c) Context Setter, namely NGOs, Indonesian Tour Guide Association (HPI) and Travel Agent Association (ASITA), Indonesian Recreational Park Business Association (PUTRI) and Event Organizer Association (AEO), Community Groups or Pokdarwis, Pokdarwis Communication Forum, KPK (Krakatau Putera Community), d) Crowd namely, Culture Office, Regional Development Planning Agency, Public Works Office, and the community